Accounting, Experiential Learning and Change: A Micro Case Study in the Field of Social Services - Chawla, Akhila (Journal of Comparative International Management, 2018)
This paper aims to report on how accounting practices are framed and implicated in experiential learning, adaptation and change processes at the micro level in one of the biggest publicly delivered social services program in India. The paper draws on Kolb (1984) and Lewin (1943) four stage experiential learning Model (ELM) to examine the role accounting plays in processes of learning, knowledge and adaptations. An attempt is made to theorise learning and adaptation that can be triggered and supported by accounting practices. Accounting processes gather meaning based on the manner in which they are enlisted in contextual and cultural environments. They are known to be not only be the change but also be the provider of the preconditions for change. In contrast to a negative enlistment of accounting in developing nations settings (Rahaman, Everett & Neu, 2007), this study argues that the accounting and accountability practices in MGNREGS create conditions for newer understandings, learning and change by providing information and concrete experiences around which communication, interactions and reflections take place and as a platform for testing, sense-making and knowledge assimilation in developing nation village settings. In effect, these accounting practices have the potential to positively shape not only organizational processes but the socio-economic life of the wider social at the micro level. Social services is an underexplored area in accounting literature and especially so in developing nation contexts. This paper introduces a social accounting perspective on learning and change at the micro citizen level in the field of social services. Also, it introduces the Experiential Learning Theory (ELT) and Kolb’s ELM as an alternative accounting framework, which has so far only been used for research in accounting education.